Television Da’wah as Popular Culture: A Review of the Symbiosis between Religion and Entertainment - Fauzan Reza Fahlevi; Roshim, Ahmad Roshim Musyaffa; Surawani, Surawani (Jurnal Studi Agama, 2025)
This study analyzes how television da’wah in Indonesia is constructed as part of popular culture through the symbiosis of religion and entertainment. Using a qualitative descriptive approach, the research examines da’wah programs through observation, content analysis, and literature review. The findings indicate that television da’wah has transformed traditional preaching into mass media communication with a wider audience, especially among urban communities and younger generations. Religious messages are combined with popular entertainment elements such as celebrities, religious music, humor, and modern visualization, making them more accessible. However, the dominance of entertainment also carries the risk of producing a shallow understanding of religion, as entertainment aspects tend to overshadow religious substance.